2022
DOI: 10.1101/2022.12.22.22283648
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analogous humoral antigen recognition between Monkeypox-infected and Smallpox-vaccinated individuals

Abstract: In early 2022, a cluster of Monkeypox (now termed MPOX) virus (MPXV) cases were identified within the UK with no prior travel history to MPXV-endemic regions, suggesting localised transmission of MPXV within the UK. Subsequently, cases were identified in several other non-endemic countries and currently exceed 80,000 worldwide, primarily affecting gay, bisexual, and other men who have sex with men. Public health agencies worldwide have offered the IMVANEX Smallpox vaccination to these individuals to provide pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 60 publications
2
3
0
Order By: Relevance
“…An ROC analysis evaluating paediatric negatives to vaccinated sera reveals a higher sensitivity (91.3 % CI:82.30-95.95) compared to those infected with Mpox (81% CI:66.58-90.78) and vaccinated and Mpox-infected individuals combined (83.9% CI:76.22-89.44) ( Table 1, Supplementary Table 1 ). This demonstrates that individuals vaccinated with IMVANEX generate a higher M1 antibody response compared to those infected, consistent with findings from previous studies 28 . Additionally, it has been observed that mRNA vaccines (VGPox1 and VGPox2, both encoding a fusion protein containing A35R and M1R) induce a rapid and robust production of MPXV M1 and A35 specific antibodies seven days after vaccination, indicating a more effective immune response to MPXV M1 compared to natural infection which induced humoral immunity against other antigens with non-significant levels of M1-specific antibodies seven days post exposure 33 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…An ROC analysis evaluating paediatric negatives to vaccinated sera reveals a higher sensitivity (91.3 % CI:82.30-95.95) compared to those infected with Mpox (81% CI:66.58-90.78) and vaccinated and Mpox-infected individuals combined (83.9% CI:76.22-89.44) ( Table 1, Supplementary Table 1 ). This demonstrates that individuals vaccinated with IMVANEX generate a higher M1 antibody response compared to those infected, consistent with findings from previous studies 28 . Additionally, it has been observed that mRNA vaccines (VGPox1 and VGPox2, both encoding a fusion protein containing A35R and M1R) induce a rapid and robust production of MPXV M1 and A35 specific antibodies seven days after vaccination, indicating a more effective immune response to MPXV M1 compared to natural infection which induced humoral immunity against other antigens with non-significant levels of M1-specific antibodies seven days post exposure 33 .…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, a subsequent decrease in antibody titres was observed ∼84 days post-dose 2 (PD2.4, Figure 2 ), suggesting a waning of the humoral immune response to MPXV and VACV antigens. A similar trend that we previously demonstrated with individual MPXV and VACV antigen ELISAs 28 . The majority of samples remain above the designated cut-off defined in this study up to 220 days post-dose two.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Finally, according to the examination specificity reaching 99%, the threshold of the A35 and A33 ELISA AUC values was 0.1155 and 0.0955 (Supporting Information: Figure ). In a previous study, Otter et al showed that both MPXV‐infected or smallpox‐vaccinated individuals contain A35‐ or A33‐specific antibodies 8 …”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, Otter et al showed that both MPXVinfected or smallpox-vaccinated individuals contain A35-or A33-specific antibodies. 8 To determine whether we could detect A33-binding antibodies induced by previous smallpox vaccination, we first performed an ELISA assay with A33 antigen and serial dilutions of the plasma samples (Figure 1A,B). The results indicated that 29% (23/79) of the samples from the hospital staff older than 42 years were positive for antibodies against A33.…”
Section: Introductionmentioning
confidence: 99%